'The More Accuracy the Better'?: Analysing Adaptation Reception in Reaction Videos. (23rd January 2018) - Rowe, Rebecca
Abstract: Casie Hermansson argues that 'There are…signs of increasing value placed on the lay perspective and thus on fidelity as a critical…tool' (149–50) because, as Dudley Andrews argues, 'Fidelity is the umbilical cord that nourishes the judgments of ordinary viewers as they comment on what are effectively aesthetic and moral values' (27). While audiences may discuss adaptations in terms of fidelity, fidelity does not have a stable meaning across all audience members. As Stam argues, 'The question of fidelity ignores the wider question: Fidelity to what?' (57). Viewers desire adaptations to remain true in different ways, and it can be difficult for producers and scholars alike to discover what exactly audiences want in a 'faithful' adaptation. Scholars need effective tools to measure how audiences perceive fidelity, and reaction videos can be one of these tools. This article traces the history of film reception studies and how changing media requires changing analysis tools. Then, it gives a general theorization of reaction videos, including what they are and the benefits and limits of using them. Finally, the article ends with a case study of reaction videos of Netflix's Lemony Snicket's A Series of Unfortunate Events to more concretely demonstrate how these videos illuminate fidelity, paying close attention to how these videos, and their comment sections, depict clashing desires around fidelity. The ultimate aim is to offer the beginnings of a new methodology that might allow scholars to interrogate the way contemporary audiences experience fidelity.